The promised land : Exodus 20:1-1 Samuel 16:19. - Hoth, Iva (Her The picture Bible for all ages ;, 1973)
Retells in comic book format the Bible stories, from the Jews' exodus from Egypt to David's anointment as the next King of Israel.